Landslide Mitigation at The Bagong Dam Abutment, Trenggalek District - Hilmawan, Gilang Bobby; Sriyana, Ignatius (Universitas Negeri Yogyakarta, 2024)
Landslides occurred continuously from July 2022 until July 2023, disrupting the construction of the Bagong Dam abutment. Geologically, the foundation of the Bagong Dam consists of a fairly thick colluvial layer, which is prone to landslides. So, the analysis of landslide mitigation at the Bagong Dam abutment is needed. The slope stability analysis carried out by Fellenius and Bishop method, then the slope modeling was carried out using Geostudio software. The analysis results on the existing slopes produced a safety factor of 0.987 (<1.07) for the Fellenius method and 1.042 (<1.07) for the Bishop method. These safety factors indicate that the existing slope is unstable and slope failure is likely to occur. In the first alternative countermeasure analysis, the slope safety factors for the cross-section of the dam at STA 0+625 were 1.715 for upstream and 1.338 for downstream; at STA 0+641, 1.321 upstream and 1.306 downstream; and for the longitudinal section of the dam, 1.525. All these safety factors greater than 1.25, indicating that the slope is stable. In the second alternative countermeasure, the slope safety factors obtained for the cross-section of STA 0+641 were 1.362 for upstream and 1.386 for downstream, and 1.657 for the longitudinal section. These safety factors are also greater than 1.25, which indicates the slope is in stable condition. The additional cost for implementing the first alternative countermeasure is 73.9 million, while for the second alternative is 35.7 million. So that, the second alternative countermeasure is the best choice by the multi-criteria decision-making analysis results.